Valproic Acid Enhanced Apoptosis by Promoting Autophagy Via Akt/mTOR Signaling in Glioma - Han, Wei (Cell Transplant, 2020)
Glioma is the most common malignant tumor in the central nervous system with a poor median survival. Valproic acid (VPA), a widely used antiepileptic drug, has been found to have antitumor effects on gliomas, but its role still has not been determined. In this study, we investigated VPA-induced apoptotic and autophagic effects on human U251 and SNB19 cells by cell counting kit-8 assay, flow cytometry, terminal deoxynucleotidyl transferase-mediated nick end labeling staining, western blots, and immunofluorescence assay in vitro, and then we further explored the role of autophagy in apoptosis by using the selective antagonist MHY1485. The data showed that VPA inhibited U251 and SNB19 glioma cells viability in a dose-dependent and time-dependent manner and induced apoptosis through the mitochondria-dependent pathway in vitro. In addition, VPA activated the Akt/mTOR pathway by decreasing their protein phosphorylation to promote cellular apoptosis. Surprisingly, the mTOR agonist MHY1485, causing a strong elevation of mTOR activity, partially reduced apoptosis ratio, which supposing that the autophagy of VPA is involved in the regulation of apoptosis. These findings suggest that VPA enhanced apoptosis by promoting autophagy via Akt/mTOR signaling in glioma, which could be further evaluated as a reliable therapy for glioma.